Competitive advantage: mediatorof intellectual capital andperformance. - Kamukama, Nixon; Ahiauzu, Augustine; Ntayi, Joseph M (Emerald Group Publishing Limited, 2011)
The purpose of this paper is to examine the mediating effect of competitive advantage in the relationship between intellectual capital and financial performance in Uganda’s microfinance institutions. The major aim is to establish the role of competitive advantage in the relationship between intellectual capital and firm performance. The paper adopts MedGraph program (Excel version), Sobeltests and the Kenny and Boran approach to test for mediation effects. Competitive advantage is a significant mediator in the association between intellectual capital and financial performance and boosts the relationship between the two by 22.4 percent in Ugandan microfinance institutions. Further findings confirmed a partial type of mediation between the intellectual capital, competitive advantage and financial performance. Only a single research methodological approach was employed and future research through interviews could be undertaken to triangulate. Furthermore, the findings from the present study are cross-sectional. Future research should be undertaken to examine the mediation effects studied in this paper across time. In order to have a meaningful interpretation of the results of there lationships between study variables, it is always vital to assess the role of the third variable(competitive advantage) in the relationship. This enables practitioners and scholars to comprehend and make legitimate decisions and conclusions that can foster business growth.This is the first study that focuses on testing the mediating effect of competitive advantage on the relationship between intellectual capital and financial performance in Ugandan de microfinance institutions.
Competitive advantage.
Keywords: Intellectual capital, Competitive advantage, Financial institutions, Financial performance,Uganda